Determination of nitrogen (N), Phosphorus (P), and Potassium (K) levels in leaves of selected oiled and un-oiled mangroves within the Taklong Island National Marine Reserve, (TINMAR), Nueva Valencia, Guimaras. - Villavelez, Jason Gonzales (2009.)
In August 11, 2006, the oil tanker M/T Solar 1, shipping almost two millions liters of bunker oil, sank in the south-western part of Guimaras Island, and it brought environmental damage to around 432 ha. of mangrove forest. To elucidate the effects of the remaining oil on the mangroves, the primary nutrients (nitrogen, phosphorus, and potassium) in the leaves of the mangroves were analyzed to determine if they can be used to monitor the sub-lethal effects of the oil on the mangroves. Differences in the nutrients between oiled and un-oiled sites and the effect of oil spill on the mangroves species were also studied. The study was conducted at selected sampling sites within TINMAR and on five (5) mangrove species (Rhizophora apiculata, R. murconata, R. stylosa, Avicennia marina, and Sonneratia alba) on two sampling periods, October 2007 and January 2008. Total nitrogen was determined using the Kjeldahl method; total phosphorus was determined using dry ashing method (BSWM), and potassium was processed by the acid digestion method and analyzed using Flame Atomic Absorption Spectrophotometry. The results of the study show that mangrove species studied in the oiled sites have significantly higher nitrogen levels, higher phosphorus content, and lower potassium concentration than the mangroves in the unaffected site. Mangrove species in the different sampling sites showed a significant increase in the concentration of nitrogen and phosphorus but a decrease in potassium concentration from the first to the second sampling period. Nitrogen levels in the leaves of the mangroves in the oiled sites are lower than the nitrogen levels of mangroves leaves under normal conditions. Phosphorus levels in the leaves of oiled mangroves are within the normal values. Potassium levels of the oiled mangroves leaves are lower than the levels of the mangroves leaves under normal conditions except Sonneratia alba which is within the normal values. Eighty six percent (86 percent) or 21 out of the 25 mangroves studied shows recovery from oil spill while fourteen percent (14 percent) or 4 out of 25 mangroves studied had not shown signs of recovery. Based on the results, primary nutrients (N, P, and K) of the mangrove leaves can be used to monitor the sub-lethal effects of the oil spill.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mangroves, Leaves -- Oiled; Mangroves, Leaves -- Un-oiled.